Perbandingan Tindakan Pegawai dan Pengunjung Tentang Kebijakan Kawasan Tanpa Rokok di Rumah Sakit Ibnu Sina Kota Makassar - Afni, Nur; Kandacong, Rika Kurnia; Batter, Sherly Rudianti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Makassar City has issued Makassar Mayor Regulation Number 13 of 2020 which regulates Non-Smoking Areas. Places included in smoking-free areas include: health service facilities, teaching and learning places, places where children play, places of worship, sports facilities, public transportation, workplaces and public places. Based on the results of an initial survey of 10 visitors at Ibnu Sina Hospital, it turns out that of the 10 visitors, 70% said they still saw other visitors smoking secretly in the Non-Smoking Area area and another 30% of visitors said they had never seen smoking activities there. Non-Smoking Area. Judging from these explanations, researchers are interested in conducting research on the description of employee and visitor actions regarding the no-smoking area policy at Ibnu Sina Hospital, Makassar City. The type of research used is quantitative research using a descriptive survey method which aims to find out a comparative picture of the actions of employees and visitors regarding the No-Smoking Area Policy at the Ibnu Sina YW-UMI Hospital, Makassar City. Based on the research results, it was found that First, the positive actions of doctors regarding the area There were 11 people (91.7%) without smoking at Ibnu Sina Hospital and 1 person (8.3%) showed negative actions. Second, 13 doctors (61.9%) showed positive actions regarding smoking-free areas at Ibnu Sina Hospital and 8 people (38.1%) showed negative actions. Third, most of the negative actions shown by patients regarding the non-smoking area at Ibnu Sina Hospital were 60 people (55.6%) and 48 people (44.4%) showed positive actions. Finally, most of the negative actions shown by the patient's family regarding the non-smoking area at Ibnu Sina Hospital were 235 people (62.5%) and 81 people (37.5%) showed positive actions.